Neighboring Plants Alleviate Aluminum Toxicity on The External Hyphae of Gigaspora margarita - AGUS ROHYADI (Microbiology Indonesia, 2009)
Excessive soluble aluminum (Al3+) in acidic soils is toxic to the external hyphae of arbuscular mycorrhizal fungi but it can be alleviated by other soil factors. A glasshouse experiment was conducted to study the effect of increased Al3+ concentration on the growth of the external hyphae of Gigaspora margarita in the presence of other plants near the host plants. The experiment used compartmentalized pots to facilitate the growth of mycorrhizal-inoculated host plants, external hyphae of the fungus and not mycorhizal-inoculated neighboring plants in different compartments; and measuring the effects of Al3+ and of the neighboring plants on the growth of the fungal hyphae independently. Increased concentration of Al3+ in soil affected the growth of external hyphae of G. margarita negatively. However, the hyphal length density of the fungus was much higher in the pots with neighboring plants than that in the other ones, despite the Al toxicity. This indicates that the hyphae could be taken away from the toxic effect of Al3+ by the stimulating growth from roots of the neighboring plants.